Links Between Body Satisfaction and Relationship Satisfaction in a Sample of Young Adult Women in Lithuania - Legkauskas, Visvaldas; Ališauskaitė, Elzė (Social Welfare: Interdisciplinary Approach, 2023)
The aim of the present study was to examine links between young adult women satisfaction with their bodies and romantic relationships. The study involved 162 young adult women aged 20–35. One hundred and nineteen women indicated that they currently had a partner and the remaining 43 participants indicated that they were single.Body satisfaction was measured using the Multidimensional Body-Self Relations Questionnaire (MBSRQ, Cash, 2000). Relationship satisfaction was assessed using the Couple’s Satisfaction Scale (Čepukienė, 2019).Results of the study indicated that adult women who had a romantic partner valued their appearance as more physically attractive and were more satisfied with their appearance than young adult women without a romantic partner. Those with a partner were more satisfied with individual body parts than women without a romantic partner. On the other hand, those in a relationship were more concerned about their body weight than single women. Satisfaction with a body and satisfaction with a romantic relationship were partly related. A more favorable assessment of one’s appearance and satisfaction in individual parts of one’s body was associated with satisfaction with emotion- and behavior-oriented interactions, as well as overall satisfaction with romantic relationships.